De la antropología a la política en el Leviatán de Hobbes (2010)
ABSTRACT:The exhibition aims to highlight the arguments the idea that the natural condition of man, as understood by Hobbes, can be thought of as a sort of anthropology of equality. The notion of natural law weaves continuity relations between the Hobbesian conception of the human and political philosophy, can sustain the hypothesis that a key function of the state is producing for civilian life, an anthropology with universal features.